2022
DOI: 10.1155/2022/5133610
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical and Tribological Characteristics of Medical Grade Ti6al4v Titanium Alloy in Addition with Corrosion Study for Wire EDM Process

Abstract: Metals used in biomedical applications are frequently coated to prevent oxidation and metallic ion release, both of which can be harmful due to toxic effects. To prevent these adverse effects of metals, researchers have focused their efforts on developing various coating techniques, facilitating surface coating, or obtaining functional surfaces. (WEDM) is now considered a difficult method of obtaining functional surfaces for medical applications. The properties of the surface and subsurface layers obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Zinc cozted brass wire was found effective in material rate improvement and recast layer reduction. Prakash et al (2022) found favourable corrosion behavior, mechanical and tribological characteristics of Ti6al4v, machined by WEDM. Kumar et al (2019) found good metallurgical properties for WEDM machined titanium.…”
Section: Review Of Past Work On Wedm Of Titanium and Alloysmentioning
confidence: 83%
“…Zinc cozted brass wire was found effective in material rate improvement and recast layer reduction. Prakash et al (2022) found favourable corrosion behavior, mechanical and tribological characteristics of Ti6al4v, machined by WEDM. Kumar et al (2019) found good metallurgical properties for WEDM machined titanium.…”
Section: Review Of Past Work On Wedm Of Titanium and Alloysmentioning
confidence: 83%
“…However, the physical features of magnesium may readily produce several processing issues and welding aws such as oxide coatings, fractures, and porosity. High thermal conductivity, melting and boiling temperatures, high solidi cation shrinkage, low viscosity, and good hydrogen solubility are just a few of magnesium's unique qualities [6]. It also has a strong tendency to oxidise and has low melting and boiling temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Our work focuses on LM4 (Al-Si hypoeutectic) alloy because of its low melting point and other decent mechanical properties, as well as its ability to retain tensile strength up to 200°C operating temperature [4]. The mechanical properties of this alloy can be improved by adding reinforcements such as TiB2, B4C, and Al2O3 [5]- [8]. We chose Si3N4 as a ceramic reinforcement for the composites fabrication in our study because it offers a favorable combination of physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%